2022
DOI: 10.2478/jvetres-2022-0003
|View full text |Cite
|
Sign up to set email alerts
|

Field trial of antibody response to inactivated bacterial vaccine in young Holstein calves: influence of animal health status

Abstract: Introduction Bovine respiratory disease (BRD) is one of the primary causes of death in young calves. Vaccination against infection by the common bacteria causing BRD is possible; however, the physical condition of the young calves that enables antibody production when stimulated by early immunisation remains to be elucidated. Material and Methods Healthy young female Holstein calves on a commercial dairy farm were fed a colos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 28 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…In this study, however, the number of calves with positive vaccine responses to M. haemolytica was low even after the booster vaccination. A previous study (6) investigating the same vaccine as used in this research reported that a higher BMI was a positive factor for successful early vaccination and that the calves with positive vaccine responses to M. haemolytica had higher BMIs (mean 70) than those responding positively to H. somni and P. multocida. Although there were slight differences in BMI between the groups, the mean BMI of the calves in this study was similar to that of the M. haemolytica-negative calves in the previous report (6).…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…In this study, however, the number of calves with positive vaccine responses to M. haemolytica was low even after the booster vaccination. A previous study (6) investigating the same vaccine as used in this research reported that a higher BMI was a positive factor for successful early vaccination and that the calves with positive vaccine responses to M. haemolytica had higher BMIs (mean 70) than those responding positively to H. somni and P. multocida. Although there were slight differences in BMI between the groups, the mean BMI of the calves in this study was similar to that of the M. haemolytica-negative calves in the previous report (6).…”
Section: Discussionmentioning
confidence: 68%
“…A previous study (6) investigating the same vaccine as used in this research reported that a higher BMI was a positive factor for successful early vaccination and that the calves with positive vaccine responses to M. haemolytica had higher BMIs (mean 70) than those responding positively to H. somni and P. multocida. Although there were slight differences in BMI between the groups, the mean BMI of the calves in this study was similar to that of the M. haemolytica-negative calves in the previous report (6). We therefore presume that the inadequate antibody response to M. haemolytica in this study is due to the low BMI of the recipient calves.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations